ANALISA PERBANDINGAN WAKTU DAN KECEPATAN TRANSFER PADA MULTI PROTOCOL LABEL SWITCHING (MPLS) DENGAN VIRTUAL PRIVATE NETWORK (VPN) UNTUK PERPINDAHAN DOKUMEN PADA JARINGAN KOMPUTER - Ibrahim Saleh; Hero Wintolo; Dwi Nugraheny (Institut Teknologi Dirgantara Adisutjipto, 2014)
MPLS (Multi Protocol Label Switching) technology has been developed and mostly used by the service provider on their main network. Data packets which forwarded from one router to another router can also use VPN (Virtual Private Network) technology. VPNs were developed in the field of computer networks now have many variants, such as MPLS VPN and VPN which connects between computers or a LAN through a public network is the internet. The purpose of this final task is build a lab scale VPN network with MPLS technology use Mikrotik router RB 750GL and create a VPN connection to the STTA campus network passing the public internet. Then do a comparative analysis of the time required and the speed of transfer on both the network. The results of a comparative analysis between MPLS and VPN with the same file capacity, it appears that the MPLS network is faster in time speed and transfer speed